Factors Associated with Changes in Quality of Life in Patients with Schizophrenia Using Atypical Antipsychotics - do Nascimento Martins, Álex Brunno; Reis, Edna Afonso; Oliveira, Helian Nunes de; Ruas, Cristina Mariano (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Introduction: Schizophrenia is a mental disorder that affects the perception and thinking of individuals. It is known that the disease involves not only life expectancy, but also the health-related quality of life (HRQoL) of the affected individuals. Studies have investigated the relationship between HRQoL and schizophrenia, but few validate the dynamics of the variations in HRQoL over time. Objective: to evaluate factors related to changes in HRQoL in patients with schizophrenia using atypical antipsychotics in the Unified Health System (SUS). Methods: The prospective open cohort research followed 152 patients for 12 months in the scope of the SCHEEA (Schizophrenia Economics and Effectiveness Assessment) project, collecting data on HRQoL, psychological symptoms, social functioning and other relevant aspects. Linear regression models were used to identify the factors associated with changes in HRQoL. Results: there was an increase of 0.049 in the participants’ average HRQoL. It was identified that worsening or instability in areas such as mobility, personal care, usual activities, pain, discomfort, anxiety, and depression were associated with lower HRQoL. It is suggested that the early identification and treatment of physical and psychological symptoms, along with the promotion of autonomy and functionality, are essential to improve the HRQoL of patients with schizophrenia in the SUS. Conclusion: This study contributes to the management of care for this population, highlighting the importance of multidimensional approaches that consider different aspects of the disease.